Case report: Spontaneous mandibular body regeneration following unilateral subtotal mandibulectomy in a 3-month-old French bulldog - Wright, Alexandra L.; Peralta, Santiago; Fiani, Nadine (Frontiers in Veterinary Science, 2023)
Objective: To document a case of spontaneous regeneration of the mandibular body following subtotal mandibulectomy in a juvenile dog. Case Summary: A 3-month-old male intact French Bulldog was presented with papillary oral squamous cell carcinoma located at the dorsal aspect of the molar region of the left mandible. Initial biopsy of the mass was performed by the primary care veterinarian. Complete clinical staging revealed no signs of metastasis. Computed tomographic images of the head showed minimal contrast enhancement of the mass with no signs of periosteal or bone involvement.Subtotal mandibulectomy was performed. Histopathology indicated complete excision of the tumor. The patient returned 8-weeks later for follow up and cleft palate surgical repair, at which time bone was noted in the mandibulectomy area on palpation. Repeat computed tomography of the head revealed complete regeneration of the left mandibular body from the level of the ramus to the mandibular symphysis. No treatment for malocclusion was necessary due to the reformation of a functional mandible.The present case demonstrates that spontaneous regeneration of the mandibular body is possible following subtotal mandibulectomy in immature dogs. Subtotal mandibulectomy is a radical procedure that can lead to long term complications including mandibular drift, malocclusion, and oral pain. This case report provides evidence that these sequelae may be mitigated or eliminated in young patients undergoing this procedure.